Hunt, A. and Marlow, H.F. (eds.) (2019). Ecology and Theology in the Ancient World. Cross-Disciplinary Perspectives - Padilla Peralta, Dan-el (ARYS. Antigüedad: Religiones y Sociedades, 2020)
HUNT, ALISA and MARLOW, HILARY F. (eds.) (2019). Ecology and Theology in the Ancient World. Cross-Disciplinary Perspectives. London: Bloomsbury Academic. 216 pp., 100,97€ [ISBN  978-1-3500-0406-1] [Book review]